2008
DOI: 10.1093/jac/dkn125
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility index of antiseptic agents by parallel assessment of antimicrobial activity and cellular cytotoxicity

Abstract: The BI presented may be a useful tool to evaluate antiseptic agents for use in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
281
0
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(307 citation statements)
references
References 44 publications
15
281
0
11
Order By: Relevance
“…Antimicrobials must exert selective toxicity against microorganisms without harming human tissues or cells. Müller and Kramer proposed using a biocompatibility index to assess the biocompatibility of antiseptics, defining it as the ratio of the concentration at which a compound kills 50% of mouse fibroblasts to the concentration at which it kills 99.9% of bacteria (Müller and Kramer, 2008). The PHMG-P biocompatibility index has yet to be calculated; however, the PHMB biocompatibility index is around 1.36-1.51, indicating superior biocompatibility compared with other general-purpose disinfectants such as chlorhexidine, povidone-iodine, and triclosan.…”
Section: Biocidal Properties Of Phmg-pmentioning
confidence: 99%
“…Antimicrobials must exert selective toxicity against microorganisms without harming human tissues or cells. Müller and Kramer proposed using a biocompatibility index to assess the biocompatibility of antiseptics, defining it as the ratio of the concentration at which a compound kills 50% of mouse fibroblasts to the concentration at which it kills 99.9% of bacteria (Müller and Kramer, 2008). The PHMG-P biocompatibility index has yet to be calculated; however, the PHMB biocompatibility index is around 1.36-1.51, indicating superior biocompatibility compared with other general-purpose disinfectants such as chlorhexidine, povidone-iodine, and triclosan.…”
Section: Biocidal Properties Of Phmg-pmentioning
confidence: 99%
“…For example, for iodine solutions, due to their in vitro cytotoxicity, a relatively low BI of 0.68 is reported, while in contrast a cytotoxic effect of cadexomer iodine according to recent studies could not be confirmed in vivo [49]. For povidone iodine, histologically detectable tissue toxicity could not be demonstrated in a controlled study [50].…”
Section: Infection Controlmentioning
confidence: 95%
“…In the use of antiseptic solutions, the characteristics of the individual substances, the type of wound (wound cavities, protein error) as well as the individual risk profile (allergies) of the patient should be taken into consideration [49,51,52].…”
Section: Antisepsis and Breakthrough Of Chronic Inflammationmentioning
confidence: 99%
“…PHMB has been shown to be equally effective as chlorhexidine in the treatment of other infections, like acanthamoeba keratitis (Lim et al, 2008). PHMB also has a slightly higher biocompatibility index (1.36 VS. 0.98), meaning that the ratio of antibacterial activity to cytotoxicity is higher with PHMB (Muller and Kramer, 2008). In vitro data suggest that PHMB is active against organisms at lower concentrations (lower minimum inhibitory concentrations and minimum bactericidal concentrations) and PHMB-impregnated gauze and foam wound dressings have also been used to prevent infection and promote wound healing in other types of wounds (e.g., surgical site infections, traumatic wounds, ulcers) (Roth et al, 2007;Andriessen and Eberlein, 2008;Valenzuela and Perucho, 2008;Penn et al, 2006;Timmons and Leak, 2010).…”
Section: Effectiveness Of Phmb-impregnated Discsmentioning
confidence: 99%